Innovation Indicator 2009: Germany Has Still Some Catching up to Do - Heike Belitz; Marius Clemens; Astrid Cullmann; Christian von Hirschhausen; Jens Schmidt-Ehmcke; Doreen Triebe; Petra Zloczysti (Weekly Report, 2010)
On behalf of the Deutsche Telekom Stiftung (Deutsche Telekom Foundation) and the Bundesverband der Deutschen Industrien (Federation of German Industries) DIW Berlin has investigated Germany's innovative capacity for the fifth time in an international comparison. The survey evaluates the ability of countries to create and transform knowledge into marketable products and services (i.e., innovations) using a system of indicators that provides an overall composite indicator of innovative capacity as well as a detailed profile of strengths and weaknesses. Of the seventeen leading industrial nations investigated under the survey Germany only ranked 9th thus remaining in the broad middle range. Relative to its most important competitors Germany looses ground. The US, followed by Switzerland, Sweden, Finland, and Denmark, headed up the list. Germany is particularly successful in its ability to network key participants in the innovation process as well as in international markets of high-technology sectors like mechanical engineering, chemical industry, vehicle manufacturing and medical instruments. Deficiencies in Germany's education and in the financing conditions for innovation and the founding of new companies, plus the regulation of product markets remain the country's greatest innovation system weaknesses.
Keywords: O30; O38; O57; 330; Innovation system; Composite indicator; Industrialized countries